El cristianismo y las mutaciones sociales del noroeste peninsular - Plácido Suárez, Domingo (Antigüedad y Cristianismo, 1990)
The ancient Christianity entered into Galicia in two waves, representatives of the process of aculturation in this area. The first wave, bearers of the Priscilianism, persisted in the violent branch of the Monks. The second wave, heir to the transformations which took place after Martin of Dumium meant the alineation of the rural system to a new facet of the Christianism which had reached again the town comming from the rural world and for that reason resuted to be effective in this same environment.